La facturación electrónica frente al recaudo tributario en Colombia (2020)
Globalization has brought with it a number of changes that are contrary to economic models and the management of all kinds within them, among these are innovative strategies such as electronic tax filing for all taxpayers in different societies. Colombia is inserted in the international trend of technological innovation, through the mandatory electronic invoicing as a collection mechanism. With a descriptive-documentary scope, this research analyzes the impact of the implementation of electronic invoicing on tax collection in Colombia. In general, electronic invoicing has an impact on tax collection. Although the obligation made a certain difference and a positive impact in relation to collection, in the case of Colombia the simple decision of its adoption did the same, while it is clear that it is not contemplated to stop establishing control actions so that this mechanism maintain and even transform towards the new needs of taxpayers, responding to its accessibility and management.